Therapeutic use of lowmolecular weight heparin for capillaritis alba - Hesse, G.; Kutzner, H. (Phlebologie, 2008)
The reason of the so called ulcerated capillaritis alba or idiopathic atrophie blanche is vasculopathy caused by severe venous hypertension. Thrombosed and rarificated vessels worsen the oxygenation, increase permanent inflammation and impede the necessary compression therapy. The anti-inflammatory effects of heparin alleviate pain and being independent from the antithrombotic ones it needs much lower doses for treatment. This anti-inflammatory effect is now becoming more important in clinical phlebology. Case studies of more than 50 patients and one prospective randomized study of 87 patients clearly demonstrate the ameliorated healing of ulcerated atrophie blanche. In our office we could document this positive effect with 22 patients. We present the pathophysiology of low molecular heparins for ulcerated capillaritis alba and our own experiences with it.
Keywords: Ulcerated capillaritis alba; vasculopathy; low molecular weight heparin; protective effects of heparin